Pointwise completeness and pointwise degeneracy of positive fractional descriptor continuous-time linear systems with regular pencils - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
Pointwise completeness and pointwise degeneracy of positive fractional descriptor continuous-time linear systems with regular pencils are addressed. Conditions for pointwise completeness and pointwise degeneracy of the systems are established and illustrated by an example.
Keywords: pointwise completeness; pointwise degeneracy; descriptor systems; fractional systems; positive systems